Boeing, Boycotts, and Most Favoured Nation: China’s Response to United State Tariffs Under WTO Law - Wijaya, R.M. Rifky Erlangga Hadi; Sofian, Muhammad; Hermono, Budi; Serfiyani, Cita Yustisia (LIBERATICA, 2025)
The violation of the Most-Favoured Nation (MFN) principle in the case of China’s boycott of American-made Boeing aircraft requires each country to provide equal trade treatment to all other members, as set out in the GATT 1994 and WTO agreements. Selective boycotts can violate this principle, primarily if the action is based on considerations of the product’s country of origin. The method used is normative legal research with a legislative and conceptual approach. The statute approach analyzes WTO provisions related to the MFN principle. In contrast, the conceptual approach examines the concept of non-discrimination in international trade law. This research conclude that the boycott of Boeing products can be considered contrary to the MFN principle if China does not apply similar policies to similar products from other countries. Justification based on national security or retaliation can only be accepted if it meets specific criteria determined by the WTO. Unilateral actions without going through the WTO dispute resolution mechanism are also considered to damage the rules-based multilateral trade order potentially. This study emphasizes the importance of compliance with the Most Favoured Nation principle and legal dispute resolution in maintaining justice and stability of international trade. The conclusion is WTO must create new regulations to govern the boundary between political actions and legitimate trade policies as a form of protection.